Measuring economic potential via the gravity model of trade - Beronilla, Nikkin (Philippine Review of Economics, 2016)
Trade is a good gauge of economic activity. Given the economic and geographical attributes of a place, one can assess the likely levels of trading activity, and this may be used as an indicator of the relative economic potential among the areas. However, trade estimates are available only at the regional level of disaggregation, despite the fact that planning by local governments and even by line agencies of the central government happens mostly at the sub-regional level. In this research, we fill this data gap by estimating trade at town or city level via a gravity model of trade. Normally sub-regional trade is estimated using Ordinary Least Regression, but this research uses Poisson Regression which is better at handling zero trade values without transformation. The research results have been applied by a number of government agencies in their respective programs.